The Effect of Work-life Balance on Employee Performance Through Job Satisfaction as an Intervening Variable - Candra Agung Prasetyo; Dewie Tri Wijayati Wardoyo (Profesional Muda Cendekia Publishing, 2023)
This study aims to measure and analyze the effect of work-life balance on employee performance through job satisfaction in commercial division employees of PT Aneka Jasa Grhadika. This research is a causal research that uses a quantitative approach, with a population consisting of 70 commercial division employees. Data analysis in this study used SEM-PLS with the help of SmartPLS3 software. This results of this study prove that work-life balance has a significant positive effect on employee performance, work-life balance has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, and job satisfaction mediates between work-life balance employee performance.